A Disproportionate Burden of Care: Gender Differences in Mental Health, Health-Related Quality of Life, and Social Support in Mexican Multiple Sclerosis Caregivers - Paul B. Perrin; Ivan Panyavin; Alejandra Morlett Paredes; Adriana Aguayo; Miguel Angel Macias; Brenda Rabago; Sandra J. Fulton Picot; Juan Carlos Arango-Lasprilla (Behavioural Neurology)
Background. Multiple sclerosis (MS) rates in Latin America are increasing, and caregivers there experience reduced mental and physical health. Based on rigid gender roles in Latin America, women more often assume caregiving duties, yet the differential impact on women of these duties is unknown. Methods. This study examined gender differences in mental health (Patient Health Questionnaire-9, Satisfaction with Life Scale, Rosenberg Self-Esteem Scale, State-Trait Anxiety Inventory, and Zarit Burden Inventory), health-related quality of life (HRQOL; Short Form-36), and social support (Interpersonal Support Evaluation List-12) in 81 (66.7% women) Mexican MS caregivers. Results. As compared to men caregivers, women had lower mental health (p=0.006), HRQOL (p<0.001), and social support (p<0.001). This was partially explained by women caregivers providing care for nearly twice as many hours/week as men (79.28 versus 48.48, p=0.018) and for nearly three times as many months (66.31 versus 24.30, p=0.002). Conclusions. Because gender roles in Latin America influence women to assume more substantial caregiving duties, MS caregiver interventions in Latin America—particularly for women caregivers—should address the influence of gender-role conformity on care and psychosocial functioning.